Modeling and simulation of single electron transistor with master equation approach. (August 2016) - Willy, Frans; Darma, Yudi
Abstract: In this paper, we discuss modeling and simulation of single dot Single Electron Transistor (SET) using master equation approximation. For SET modeling and simulation, master equation method treats the electron tunneling and its transition probabilistically. The probability of electron tunneling is used to determine the current density in accordance with selected input parameters. The calculation results show fairly accurate electrical characteristics of SET as compared with experimental data. Staircase pattern from I-V are clearly obtained as the main role of coulomb blockade effect in SET system. We also extend our calculation by introduce some additional parameters such as; the effect of working temperature, gate voltage dependent, and the influence of resistance to the device characteristic. We found that increasing operational temperature will promote higher current density, both in forward and reverse bias region. In the case of using single dot with 30 nm × 80 nm × 125 nm dimension, coulomb blockade effect could be reduced by applying gate voltage higher than 3V and setting drain resistance higher than source's. Our studies show an alternative approach in modeling and simulation of electronic devices and could be potential for development of novel nanoelectronic devices.